1993
DOI: 10.1021/np50095a005
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Agents, 138. Rotenoids and Isoflavones as Cytotoxic Constituents from Amorpha fruticosa

Abstract: Eight cytotoxic compounds have been isolated from the CHCl3 extract of Amorpha fruticosa. One compound, 6'-O-D-beta-glucopyranosyldalpanol [10], is a new cytotoxic rotenoid. Another known rotenoid, 12 alpha beta-hydroxyamorphigenin [6], was first shown to exhibit extremely potent cytotoxicity (ED50 < 0.001 microgram/ml) in six neoplastic cell lines. In addition to these compounds, three isoflavones (afrormosin [1], 7,2',4', 5'-tetramethoxyisoflavone [2], 8-methylretusin [3]) and five rotenoids (amorphispironon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 6 publications
2
55
0
Order By: Relevance
“…15,16) In general, hydrophilic compounds with sugar moieties are hardly permeable to the cellular membranes. 17) Tectorigenin induced differentiation into granulocytes and/or monocytes/macrophages, as assessed by NBT reduction, latex beads phagocytic activity and CD14 and CD66b antigen expression, and by apoptosis, as assessed by increase in hypodiploid population and DNA ladder formation, of human promyelocytic leukemia HL-60 cells less effectively than genistein. Genistein is well known to have potent PTK inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) In general, hydrophilic compounds with sugar moieties are hardly permeable to the cellular membranes. 17) Tectorigenin induced differentiation into granulocytes and/or monocytes/macrophages, as assessed by NBT reduction, latex beads phagocytic activity and CD14 and CD66b antigen expression, and by apoptosis, as assessed by increase in hypodiploid population and DNA ladder formation, of human promyelocytic leukemia HL-60 cells less effectively than genistein. Genistein is well known to have potent PTK inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Amorpha fruticosa L. root contains the prenylated flavanone, isoamoritin (Ohyama et al 1998). Three different isoflavones and five different rotenoids were purified from Amorpha fruticosa L. (Li et al 1993). One flavonoid glycoside, one ester compound and two rotenoid compounds were purified from its fruit .…”
Section: Introductionmentioning
confidence: 99%
“…Five-micron-thick sections, including the epidermis, the dermis, and the subcutaneous panniculus carnosus muscle, were mounted on glass slides, dewaxed, rehydrated in distilled water, and stained with hematoxylin and eosin(HE). All subsequent analyses were performed by an experienced pathologist without knowledge (Petkov et al, 1983;Li et al, 1993). The results of present study using wound healing experiments in animal models, biochemical analysis of wound biopsy, and in vitro studies showed that three different compounds isolated from the fruits of Amorpha fruticosa L. have antibacterial activity and promote the healing of wounds.…”
Section: Histological Examinationmentioning
confidence: 69%